Synergic activity of Cel8Pa β-1,4 endoglucanase and Bg1Pa β-glucosidase from Paenibacillus xylanivorans A59 in beta-glucan conversio - Ghio, Silvina; Bradanini, María B.; Garrido, Mercedes Maria; Ontañon, Ornella Mailen; Piccinni, Florencia Elizabeth; Marrero Diaz De Vill, Rubén; Talia, Paola Mónica; Campos, Eleonora (Elsevier, 2020)
In the efficient bioconversion of polysaccharides from lignocellulosic biomass, endoglucanases and β-glucosidases are key enzymes for the deconstruction of β-glucans. In this work, we focused on a GH8 endoglucanase (Cel8Pa) and a GH1 β-glucosidase (Bg1Pa) from Paenibacillus xylanivorans A59. Cel8Pa was active on a broad range of substrates, such as β-glucan from barley (24.5 IU/mg), lichenan (17.9 IU/mg), phosphoric acid swollen cellulose (PASC) (9.7 IU/mg), carboxi-methylcellulose (CMC) (7.3 IU/mg), chitosan (1.4 IU/mg) and xylan (0.4 IU/mg). Bg1Pa was active on cellobiose (C2) and cellooligosaccharides up to C6, releasing glucose as the main product. When both enzymes were used jointly, there was a synergic effect in the conversion rate of polysaccharides to glucose. Cel8Pa and Bg1Pa presented important properties for simultaneous saccharification and fermentation (SSF) processes in second generation bioethanol production, such as tolerance to high concentration of glucose and ethanol.